Effect of transcutaneous irradiation under the radial artery on hemodynamic variables in hypertensive patients: Double-blind clinical study - Isabella, Adriana Paula Jordão; Ocon, Carlos Alberto; Douradinho, Christian; Braga, Cristina; Lazzareschi, Leandro; Filho, Alfredo Ribeiro; da Cunha, Márcio Fernandes; Cavalcante , Fabrício Vieira; Filoni, Eduardo; Aragão, Neylor Rodrigo Oliveira; Almeida, Jacqueline Cunha Cabral Azevedo; Santos, Gleyce Kelly de Brito Brasileiro; et al. (Seven Editora, 2024)
Systemic Arterial Hypertension (SAH) is a multifactorial clinical condition, with a high rate of morbidity and mortality and low control rates. Although photobiomodulation (FBM) is capable of inducing a photobiological interaction inside cells and modifying the micro and macrovascular response in situ, there is a lack of studies that evidence its systemic effect, especially clinical and placebo controlled. Thus, this study aimed to evaluate the modulatory effects on blood pressure control in hypertensive patients after transcutaneous photobiomodulation of the radial artery. To this end, 44 participants were randomly divided into 4 groups, one group irradiated for 60 minutes a day, for 5 days, being repeated after 20 days with a total of 3 cycles (Group A), and their respective placebo (Group B); the third group was irradiated for 30 minutes a day, for 10 days, and repeated after 20 days, also totaling 3 cycles (Group C), and their respective placebo (Group D). All participants remained with previously instituted conventional drug treatment. Before the interventions, after each cycle and at the end of the interventions, blood pressure and heart rate were measured. Before and at the end of the interventions, blood samples were collected to measure interleukins 6 and 1beta. Statistical analysis was performed to compare the groups in each phase of treatment, with a= 0.05. Modulatory effects were evidenced in the control of blood pressure in hypertensive patients after photobiomodulation. Group A showed a better response to the reduction of hemodynamic variables than group C. Multidisciplinary care may have increased the adherence to treatment of all participants, including the placebo groups, which also showed a decrease in the values of hemodynamic variables. DOI:https://doi.org/10.56238/sevened2024.026-065